Changes in Disease Behaviour and Location in Patients With Crohn's Disease After Seven Years of Follow-Up: A Danish Population-based Inception Cohort. (9th October 2017) - Lo, B; Vester-Andersen, M K; Vind, I; Prosberg, M; Dubinsky, M; Siegel, C A; Bendtsen, F; Burisch, J
Abstract: Background and Aim: Crohn's disease [CD] is a progressive inflammatory bowel disease that can lead to complications such as strictures or penetrating disease, and ultimately surgery. Few population-based studies have investigated the predictors for disease progression and surgery in CD according to the Montreal classification. We aimed to identify clinical predictors associated with complicated CD in a Danish population-based inception cohort during the biologic era. Methods: All incident patients with CD in a well-defined Copenhagen area, between 2003 and 2004, were followed prospectively until 2011. Disease progression was defined as the development of bowel stricture [B2] or penetrating disease [B3] in patients initially diagnosed with non-stricturing/non-penetrating disease [B1]. Associations between disease progression and/or resection, and multiple covariates, were investigated by Cox regression analyses. Results: In total, 213 CD patients were followed. A total of 177 [83%] patients had B1 at diagnosis. Patients who changed location had increased risk of disease progression (hazard ratio [HR] = 3.1, 95% CI: 1.12, 8.52). Biologic treatment was associated with lower risk of change in location [HR = 0.3, 95% CI: 0.1–0.7]. Colonic involvement [L2 or L3 vs L1] was associated with a lower risk of surgery (HR = 0.34/0.22, 95% CI: [0.13, 0.86]/[0.08, 0.60]). All CD patients who progressed in behaviour or changed location had an increased risk of surgery [ p < 0.05] Conclusions: This population-based inception cohort study demonstrates that changes in disease location or behaviour in patients with CD increase their risk of resection. Our findings highlight the protective effect of biologic treatment with regard to change in disease location, which might ultimately improve the disease course for CD patients.